2017
DOI: 10.14483/16579089.9953
|View full text |Cite
|
Sign up to set email alerts
|

La educación matemática inclusiva: una experiencia en la formación de estudiantes para profesor

Abstract: En este artículo se muestra una experiencia de formación de estudiantes para profesor de matemáticas en y para la diversidad, de la Licenciatura en Educación Básica con Énfasis en Matemáticas - Lebem, de la Universidad Distrital Francisco José de Caldas. La experiencia tiene como propósito la colaboración mutua y solidaria en contextos de diversidad, para hacer posible el acceso a la matemática a todos los niños, niñas y jóvenes de la educación básica y media de dos instituciones educativas públicas de la ciud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Attention to diversity therefore played an important role in their teaching practice, although they recognized that truly achieving sufficient attention to diversity in secondary education could be a utopian goal. Despite considering it difficult to implement the approaches to attention to diversity proposed in current laws on education, the preservice teachers called special attention to the favorable attitude parents have to their children's education, as they believe that paying high-quality attention to diversity enriches the whole education community [1,36,42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attention to diversity therefore played an important role in their teaching practice, although they recognized that truly achieving sufficient attention to diversity in secondary education could be a utopian goal. Despite considering it difficult to implement the approaches to attention to diversity proposed in current laws on education, the preservice teachers called special attention to the favorable attitude parents have to their children's education, as they believe that paying high-quality attention to diversity enriches the whole education community [1,36,42].…”
Section: Discussionmentioning
confidence: 99%
“…Forlin and Chambers [16], Sharma et al [12], Da Silva [37] and Struyven [20] argue that attitudes toward attention to diversity improve among graduate students, who are more qualified, as they advance in their education. Along these lines, other studies [1,[38][39][40][41][42] show that the training of secondary education teachers is insufficient, especially in attention to underperforming students, lack of motivation toward studies [43], anti-social or unhealthy behavior, or school bullying. Studies by Sandoval Mena [44] and Smets and Struyven [20] find educational gaps in identification of learning difficulties, teachers' responsibilities, and cooperation among teachers.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Todo currículo presenta varias asignaturas a cursar durante un período lectivo y como parte del proceso formativo nos encontramos con un área catalogada por muchos un poco compleja la llamada matemática, misma que se encuentra inmersa día a día en el aula de clase es allí donde el docente debe aplicar buenas estrategias para fomentar un entorno agradable que fomente un aprendizaje significativo en cada estudiante y más aún en aquellos que poseen alguna necesidad educativa especial. (Castro & Torres, 2016) expresa que la matemática se considera un poco compleja para estudiantes con o sin alguna necesidad debido a la metodología del docente, a su vez expresa que la enseñanza de la matemática debe girar en torno a situaciones de aprendizaje, modelos matemáticos, uso de herramientas tecnológicas, entre otros de manera que estos sean aplicables y prácticos, dicho esto se debe cambiar el paradigma de enseñanza tradicional y hacer del aula de clase un entorno didáctico y reflexivo, así mismo (García-Oliveros & Romero-Rey, 2018) comparte criterios similares enfocadas a la realidad y que sean útiles a lo que llama 'matematizar' por consiguiente es importante que el docente se prepare y mejore sus prácticas pedagógicas en la asignatura de la matemática optimizando su entorno y a los medios digitales.…”
Section: Matemática Y La Inclusiónunclassified
“…Other studies [27][28][29] show a lack of training of secondary education professionals, especially in terms of their attention to students with low participation, demotivation towards studying [30], antisocial and unhealthy behaviors, or bullying. Smets et al [25] and Sandoval-Mena [31] found formative deficiencies in the identification of learning difficulties, teachers' responsibilities, and cooperation among them.…”
Section: Introductionmentioning
confidence: 99%